2010
DOI: 10.1136/ard.2009.127324
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cartilage loss at the wrist in rheumatoid arthritis using a new MRI scoring system

Abstract: This MRI cartilage score demonstrated excellent reliability when tested in a three-reader system. However, cartilage loss in early RA could not be distinguished from that seen in healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 14 publications
8
53
0
5
Order By: Relevance
“…These values can be compared to the ICC of 0.18 initially reported by the OMERACT initiative [30] . Significantly, they are similar to those reported using the recent MRI scoring system related to cartilage narrowing in the wrist of patients with RA [1] , indicating that the reproducibility of our quantitative approach is similar to what has been obtained for a scoring system, a qualitative approach by definition [1] . The corresponding coefficients of variation were also similar using both techniques.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…These values can be compared to the ICC of 0.18 initially reported by the OMERACT initiative [30] . Significantly, they are similar to those reported using the recent MRI scoring system related to cartilage narrowing in the wrist of patients with RA [1] , indicating that the reproducibility of our quantitative approach is similar to what has been obtained for a scoring system, a qualitative approach by definition [1] . The corresponding coefficients of variation were also similar using both techniques.…”
Section: Discussionsupporting
confidence: 71%
“…These sequences provide high spatial resolution within an acceptable acquisition time, i.e., about 5 min. This type of sequence has already proved its Table 2 Quantitative measurements of cartilage 1 Significantly different than the corresponding measurement using the VIBE sequence. Values are presented as means ± SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional MRI, cartilage damage is made visible as a volume loss slowly developing over years [32]. Especially in the early course of RA, cartilage loss in morphological MRI may be absent [33]. The lack of sensitivity of conventional MRI to assess cartilage damage in RA has triggered the application of molecular MRI of cartilage [16,34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that MRI can reveal improvement in tenosynovitis in response to treatment [ 17 ]. Scoring systems based on MRI have defi ned to grade the cartilage changes in patients with early RA [ 18 ]. In addition, bone edema on MRI has been shown, in patients with early disease, to predict who goes on to develop radiographic damage and may help identify patients who could benefi t from a more aggressive treatment [ 19 ].…”
Section: Clinical Presentation and Evaluationmentioning
confidence: 99%